2018
DOI: 10.3390/nu10111641
|View full text |Cite
|
Sign up to set email alerts
|

First Insights into the Gut Microbiota of Mexican Patients with Celiac Disease and Non-Celiac Gluten Sensitivity

Abstract: Gluten-related disorders (GRDs) are common chronic enteropathies and increasing evidence suggests an involvement of the gut microbiota. We examined the gut microbiota in Mexican people afflicted with GRDs. Ultra-high-throughput 16S marker sequencing was used to deeply describe the duodenal and fecal microbiota of patients with celiac disease (CD, n = 6), non-celiac gluten sensitivity (NCGS, n = 12), and healthy subjects (n = 12) from our local area. Additionally, we also investigated the changes in gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 62 publications
3
37
1
Order By: Relevance
“…A study conducted in the Netherlands [14] reported that the most frequent intestinal symptoms in NCGS were bloating (almost 80%) and abdominal discomfort (more than 50%), which is similar to the study conducted in Mexico [21], in which the most frequent intestinal symptoms were bloating (81%) and abdominal discomfort (42%). The Mexican study showed that these symptoms were mitigated by following a GFD for four weeks (bloating: 25%; abdominal discomfort: 14%) in NCGS patients (N = 12) [21].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A study conducted in the Netherlands [14] reported that the most frequent intestinal symptoms in NCGS were bloating (almost 80%) and abdominal discomfort (more than 50%), which is similar to the study conducted in Mexico [21], in which the most frequent intestinal symptoms were bloating (81%) and abdominal discomfort (42%). The Mexican study showed that these symptoms were mitigated by following a GFD for four weeks (bloating: 25%; abdominal discomfort: 14%) in NCGS patients (N = 12) [21].…”
Section: Discussionsupporting
confidence: 70%
“…Researchers have been attempting to characterize the NCGS rates in different countries [2,8,12,13,14,15,16,17,18]. In Latin America, there are few data about the prevalence or characterization of NCGS [15,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Mazcorro et al [ 131 ] assessed the gut microbiota of Mexican patients affected by CD ( n = 6), NCG/WS ( n = 12) and healthy subjects ( n = 12). Both the duodenal and the fecal microbiota of patients and controls were analyzed by ultra-high-throughput 16S rRNA gene marker sequencing.…”
Section: Gfd Effects On Microbiota Of Ncg/ws Patientsmentioning
confidence: 99%
“…The data characterizing the gut microbiota in coeliac disease patients was derived from both fecal samples and duodenal mucosa biopsies in studies done mostly in children with coeliac disease [64,[70][71][72][73][74][75][76][77][78][79][80][81] with fewer studies being done in adults [78,[82][83][84][85]. These studies showed differences in the microbial composition of fecal and duodenal samples in children and adults when comparing active coeliac disease with patients with treated coeliac disease, or healthy controls [86].…”
Section: Characteristics Of the Gut Microbiota In Coeliac Diseasementioning
confidence: 99%